Dielectric properties and ac conductivity of TlSbTe2 thin films - Deger, D.; Ulutas, K.; Yakut, S.; Kara, H. (ELSEVIER SCI LTD, 2015)
We report on dielectric properties and ac conductivity of the TlSbTe2 thin films grown by thermal evaporation on glass substrates at temperature range 293-373 K and measured over frequency range between 10 Hz and 100 kHz. The thicknesses of the films were between 200 angstrom and 4000 angstrom. It was found that dielectric constant (epsilon(1))of the TlSbTe2 films changes between 39 and 740 and dielectric loss (epsilon(2)) between 51-12,000 at 1 kHz and 293 K. The dielectric constant and dielectric loss were found to decrease with increasing frequency and to increase with increasing temperature. The dielectric constant exhibits bulk characteristics as the thickness exceeds 2000 angstrom. The ac conductivity follows sigma(omega)alpha omega(s) relation at frequencies higher than 1 kHz, and the dominant conduction mechanism is found to obey the Correlated Barrier Hopping (CBH) mechanism. At frequencies lower than 1 kHz, the electrical conduction is found to be in accordance with dc conduction mechanism. Analyzing the ac conductivity results, we show that as temperature increases, density of states near fermi level also increses from 1019 to 1021 cm(-3). Using frequency dependence of the dielectric constant, the maximum barrier height (W-m), its temperature and thickness dependences are determined. The values for these parameters seem to agree with the theory of classical hopping of charge carriers over a potential barrier. XRD analysis reveal that crystal structure of bulk TlSbTe2 is rhombohedral, whereas TlSbTe2 thin film is found to be amorphous structure. Morever, the temperature coefficients of capacitance (TCC) and permittivity (TCP) were investigated for thin films of TlSbTe2. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Semiconductors; Thin films; Dielectric properties; TlSbTe2; AC conductivity; RELAXATION; GROWTH; Engineering; Materials Science; Physics